Handbook of nuclear engineering. Vol 1-4 - Cacuci, Dan Gabriel (Springer, 2013)
This is an authoritative compilation of information regarding methods and data used in all phases of nuclear engineering. Addressing nuclear engineers and scientists at all levels, this book provides a condensed reference on nuclear engineering since 1958.